Ethical decision-making levels of oncology nurses - Baysal, Ebru (Nursing ethics, 2019)
Aim:This study was carried out in order to determine ethical decision-making levels of oncology nurses.Ethical Consideration:Research Ethics Committee's approval was obtained prior to the data collection. Permission to use the Turkish version of the Nursing Dilemma Test was received from Birgül Cerit. Written approval was taken from school administrators to conduct the study confirming that there were no invasive procedures planned for human beings during the study period. The study was conducted in accordance with the Helsinki Declaration. Verbal consent was obtained from each of the nurses who agreed to participate after they were informed about the study content.Method:The population of this study conducted in a descriptive way consisted of a total of 96 nurses working at the oncology units and outpatient chemotherapy units of four different hospitals between September 2017 and March 2018. The study sample included 60 nurses who responded to the question form. The data of the study were collected using “Nurses Information Questionnaire” and “Nursing Dilemma Test” developed by Crisham in 1981.Results:Oncology nurses’ mean scores in Principled Thinking (49.00 ± 6.46) and those in Practical Considerations (18.35 ± 4.47) were found to be above the moderate level. It was determined that the oncology nurses participated in the study were familiar with situations similar to the dilemmas included in the Nursing Dilemma Test (15.00 ± 4.20).Conclusion:It was concluded that oncology nurses try to take ethical principles into consideration but are also affected by environmental factors while making decisions concerning ethical dilemmas. The most frequently encountered ethical dilemmas by oncology nurses include the following: deciding not to perform cardiopulmonary resuscitation, telling the truth to the patient, studies being carried out without the patient’s content, and patient’s refusal of treatment. In order to improve oncology nurses’ critical thinking and ethical decision-making skills, it is important to determine ethical dilemmas encountered by oncology nurses, and nurses should be encouraged to be involved in ethical decision-making process through cooperation with the other healthcare personnel.